The Fractal Geometry of Growth: Fluctuation–Dissipation Theorem and Hidden Symmetry - Petrus H. R. dos Anjos; Márcio S. Gomes-Filho; Washington S. Alves; David L. Azevedo; Fernando A. Oliveira; Fernando A. Oliveira (Frontiers in Physics, 2021)
Growth in crystals can be usually described by field equations such as the Kardar-Parisi-Zhang (KPZ) equation. While the crystalline structure can be characterized by Euclidean geometry with its peculiar symmetries, the growth dynamics creates a fractal structure at the interface of a crystal and its growth medium, which in turn determines the growth. Recent work by Gomes-Filho et al. (Results in Physics, 104,435 (2021)) associated the fractal dimension of the interface with the growth exponents for KPZ and provides explicit values for them. In this work, we discuss how the fluctuations and the responses to it are associated with this fractal geometry and the new hidden symmetry associated with the universality of the exponents.